An open label randomized controlled trial on the efficacy of adding intranasal fentanyl to intravenous tramadol in patients with moderate to severe pain following acute musculoskeletal injuries - Shaharudin , Abdul Aziz (2016)
Intra-nasal fentanyl, as an alternative route of analgesic administration, has been shown to be effective particularly in pediatric population and in prehospital setting. Studies on such use among adult patients in emergency department are limited. An open-label study was conducted to evaluate the effectiveness of adding 1.5 mcg/kg intranasal fentanyl on top of 2 mg/kg intravenous tramadol (FENTANYL_TRAMADOL, n=10) as compared to 2 mg/kg intravenous tramadol alone (TRAMADOL,n=10) in adult patients with acute musculoskeletal injuries in moderate to severe pain. When analyzed using independent t-test, the mean visual analog scale (VAS) difference between pre and 10 minute post-intervention was found to be 29.8 mm (SD+/-8.4mm) in the FENTANYL_TRAMADOL arm and 19.6 mm (SD+/-9.7mm) in the TRAMADOL arm [t(8) = 2.515, p = 0.022, 95% confidence interval (CI) 1.68 to 18.72 mm]. A significantly greater albeit transient reduction in mean arterial pressure 10 minutes post-intervention was noted in the FENTANYL_TRAMADOL arm as compared to those in the TRAMADOL arm (13.35 mmHg vs 7.65 mmHg, using Mann-Whitney U test with U-value = 21.5; p = 0.029; r= 0.48). Patients in the FENTANYL_TRAMADOL arm also experienced a higher incidence of transient dizziness 10 minutes post-intervention. Although effective, intranasal fentanyl in adult patients may not be ready for primetime as it may result in significant reduction in blood pressure.